2006
DOI: 10.1007/s00264-006-0200-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the use of the humerus intramedullary nail and dynamic compression plate for the management of diaphyseal fractures of the humerus. A randomised controlled study

Abstract: The aim of this study was to compare the results of the humerus intramedullary nail (IMN) and dynamic compression plate (DCP) for the management of diaphyseal fractures of the humerus. Forty-seven patients with diaphyseal fracture of the shaft of the humerus were randomised prospectively and treated by open reduction and internal fixation with IMN or DCP. The criteria for inclusion were grade 1 or 2a compound fractures, polytrauma, early failure of conservative treatment and unstable fractures. The patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
156
4
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(188 citation statements)
references
References 16 publications
21
156
4
7
Order By: Relevance
“…Radial nerve-related complications have been quoted as approaching 3% in humeral dynamic compression plating (DCP) [2]. In their study the authors reported nerve-related complications as being 4.1% and 4.7% in DCP and intramedullary nailing (IMN) [3]. Thus, we feel that the nerve-related complications are not a point against plating.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Radial nerve-related complications have been quoted as approaching 3% in humeral dynamic compression plating (DCP) [2]. In their study the authors reported nerve-related complications as being 4.1% and 4.7% in DCP and intramedullary nailing (IMN) [3]. Thus, we feel that the nerve-related complications are not a point against plating.…”
mentioning
confidence: 95%
“…2. The authors mention implant removal, usually at 12 months, in their Methods section [3]. We would like to know whether implants were removed from all the patients or only from a selected group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of humeral shaft nonunion is often complex and technically demanding. The last decade has witnessed much technical improvement in various internal fixation devices and surgical approaches for the treatment of humeral shaft nonunion, including the application of cancellous bone grafting plus dynamic compression plate, intramedullary nails, external fixation frames and transplantation of vascularised bone graft [1,2,5,17,19].…”
Section: Introductionmentioning
confidence: 99%
“…A randomised controlled study." with great interest [1]. In their study, the authors compared the results of the humerus intramedullary nail (IMN) in 23 patients and the dynamic compression plate (DCP) in 24 patients for the management of diaphyseal fractures of the humerus.…”
mentioning
confidence: 99%